Access to information and participant in communication - Dean Armando Malay (2008)
They knew that in a few years, the land is going to settle down and all the buildings will go down. And that is what is happening now.1 But what did they do? They spent hundreds of millions of pesos to build those edifice and now, they are crumbling. who are the sufferers? it is not Mrs. Marcos J she had her moments of glory when she view them at the foyer in her beautiful terno. who suffered? The people from whom the taxes were taken. This is an example and i can multiply that by dozens of other examples of government projects which were imposed on the people without asking them first about alternatives, problems etc. so, this is the second one. The flow from top to bottom and the bottom to top. This is the hard problem of communication.